The Battle of Iwo Jima began 80 years ago. Listen to recordings from the frontlines - Ulaby, Neda (2025)
The Library of Congress preserved recordings from Marine Corp combat correspondents at Iwo Jima that included interviews with soldiers, music and the sounds of war.